Water and agriculture vulnerability to climate change and adaptive capacity in southern Africa. - Nhamo, L.; Chilonda, Pius (Water Institute of Southern Africa, 2012)
Increasing temperatures and declining rainfall patterns as well as increasing frequency of extreme climate events such as droughts and floods are the expected future weather patterns within the tropics. Africa, particularly Southern Africa, is projected to be the region most vulnerable to the impacts of climate variability and change especially in agriculture and water. This has dire consequences as most people in Southern Africa depend on agriculture for their livelihoods. While much of climate change studies have been done at global scale, the impacts of climate change and variability will be felt locally at household, community,national and regional levels. In most cases adaptation occurs at local level in ways that are usually unnoticed and unaided by national governments or international organisations. This paper down-scales the vulnerability of and adaptive capacity to climate change and variability to local level (household, community, national and regional) applying the Household Economy Approach (HEA). The focus is on local dimensions of climate change impact on water availability and agriculture productivity in Southern Africa, but taking only a sample of the region. In addition, an assessment of the factors that determine the capacity of local communities to deal with current and future climate changes and variability is made. Adaptive measures are also recommended, paying special attention to the role of local institutions in adapting to climate change. This paper emphasises the importance of ensuring that farmers have access to relevant knowledge and information on the effects of climate variability and change in order to enhance their adaptive capacity.